Sensorless Control Analysis of Electric Motor Drives Based on High-Frequency Signal Injection and Its Simulation Verification - Duhancik, Michal; Coranic, Tomas; Gaspar, Stefan; Lipovsky, Vladimir (Actuators, 2022)
The subject of this research is the sensorless control method verification of an asynchronous motor by a simulation in the area of low speed (up to 5 Hz) via the high-frequency analog signal injection method. The implementation of the continuous signal injection method is simpler when compared with the discrete signal injection; however, the discrete signal injection method has more advantages in signal processing. The injected analog signal will be superimposed on the main stator voltage. The response to this signal will be manifested mainly based on the asymmetries of the asynchronous motor, which are given by the design of the motor. The influence of the stator inductance LS will be suppressed by a suitable elimination method since this asymmetry is undesirable for the rotor position detection. The asymmetry caused by the rotor slotting will be used to detect the rotor position. The less the rotor slots are inclined, the stronger the asymmetry. Therefore, to verify the given estimation method as realistically as possible, a mathematical model of an asynchronous motor, including asymmetries due to magnetic core saturation and asymmetries due to rotor slotting, has been designed in order to get as close as possible to the real condition. Thus, the chapter “Asymmetry Creation due to Rotor Slotting” describes the given phenomenon in more detail. Subsequently, the INFORM method the rotor position detection is implemented and defined in the chapter: “Rotor Position Estimation Based on HF Signal Injection.” Given the fact that the asymmetries caused by magnetic core saturation are undesirable, he estimation error reaches up to 10%; therefore, saturations are suppressed by a convenient method. After filtering out these asymmetries, the control accuracy is achieved with the maximum rotor position estimation error of 0.05 rad, representing 1%. The inaccuracy is directly proportional to the rotor rotation speed, and it is also caused by the computing power, the processing frequency, and the complexity of the computing algorithm. The present research paper serves essentially to verify the sensorless method based on a high-frequency signal injection and as a basis for effectiveness and efficiency compared with other control methods.